PENGARUH BRAND PASSION, BRAND COMMITMENT DAN BRAND INTIMACY TERHADAP REPURCHASE INTENTION, POSITIVE WOM DAN PAY PRICE PREMIUM - Ali Wardhana; Samuel Shwan Tera (Business Management Journal, 2020)
Amid the pressures of industrial competition, emotions from consumers can be an unlimited resource that can create good opportunities. A brand can no longer be seen merely as an identity but as a relationship with consumers. Therefore, manufacturers are expected to wrap these emotions into a brand through the brand love concept. The usage of the concept of brand love is not without reason, but because brand love is the best representation of high-level constructs, one of which includes emotions. Thus this research aims to see how brand passion, brand intimacy and brand commitment build brand love and then have an impact on repurchase intentions, positive WOM and willingness to pay at premium prices on Samsung brands. This study uses primary data obtained through random questionnaire distribution and using target respondents of Samsung brand smartphone users. The results of this study indicate that brand love can be built well by brand passion, brand intimacy and brand commitment which are its dimensions. Brand love also shows that there is a positive relationship with intention to repurchase, positive WOM and willingness to pay at premium price. If it is more detailed then this study can conclude that brand commitment has the biggest contribution in building brand love and the biggest impact of brand love is positive WOM